Clinician perspective on parental empowerment in family‐based treatment for adolescent anorexia nervosa. Issue 4 (14th January 2016) - Dimitropoulos, Gina; Freeman, Victoria E.; Lock, James; Le Grange, Daniel
Abstract : This qualitative study explored which core principles of family‐based treatment (FBT) for adolescents with anorexia nervosa (AN) are perceived as most necessary for FBT to be effective in clinical practice. Paediatric interdisciplinary teams were recruited to discuss the delivery of FBT in eating disorder programmes in Ontario, Canada ( N  = 6). Thematic analysis was used to analyze the data generated from focus groups. Three major themes emerged: (i) parental empowerment (PE) is the most salient principle of FBT; (ii) various adolescent, parental and family factors are viewed as interfering with or enhancing PE; (iii) a variety of clinical interventions are utilized by clinicians to cultivate and increase PE. PE is identified as essential for adolescents with AN to successfully recover. Greater focus on addressing barriers to empowering parents is needed throughout FBT. Future studies should include measurements of PE to ascertain effects on treatment outcomes. Training and supervision protocols focused on promoting PE are recommended. Practitioner points: PE is the most salient principle of FBT. Strategies to enhance PE in phase 1 are imperative if there has been a long illness duration or parents experience mental health issues/burnout. Special clinical attention to individual factors is recommended: comorbid diagnoses, affect dysregulation and enduring eating disorder symptoms. Efforts to enhance parental involvement throughout the treatment is paramount to supporting adolescents to recover from AN.